ANALISIS KREDIT USAHA RAKYAT (KUR) PADA BANK BRI UNIT TABEK PATAH CABANG BATUSANGKAR SUMATERA BARAT - Hafiza Hafiza Arisandi; Caska '; Gani Haryana (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract:This study aimed to analyze the People's Business Credit (KUR) At Bank BRI Unit Tabek Patah Cabang Batusangkar Sumatera Barat. The analysis technique used is descriptive method is a method that describes a phenomenon based on data obtained from the documentation and interviews with PA (Executive Academic) KUR BRI Unit Tabek Patah Cabang Batusangkar Sumatera Barat. Results of research conducted at the Bank BRI Unit Tabek Patah Cabang Sumatera Barat showed that the number of Customers who apply for loans at BRI KUR Tabek Patah Sumatera Barat before and after rate cut are customer deposits rising 23.37%. Where 39.83% of customers aged between 25 years to 34 years, 43.30% type of business carried on by the customer is a business in agriculture. 56.92% of customers have a high school level education last. While the amount of business income each month is between Rp. 3,000,001 to Rp. 4,000,000 as many as 65.63%.Key Words: Kredit Usaha Rakyat (KUR)